2020
DOI: 10.1017/s0007114520004973
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary linoleic acid altered intestinal barrier function in domestic pigeons (Columba livia)

Abstract: Linoleic acid (LA) is predominantly essential for poultry. Poultry lacking LA show retarded growth and reduced disease resistance. Intestinal barrier function plays an important role in pigeon squab growth, whereas research on the effects of LA on intestinal health in altrices is scant. Considering that squabs are fed by their parents, the study aimed to explore the effects of maternal dietary LA on intestinal morphology, tight junction proteins, immune cytokines and microbial flora in squabs. A completely ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Polyunsaturated fatty acids ( PUFA ), mainly linoleic acid, affect the activity of transcription factors that control the expression of tight junction genes such as CLDN-1 and OCLN, as the result contribute the integrity and permeability of epithelial barrier ( Xu et al, 2021 ). The PUFA content of diet supplemented by BSFLO-SCa was dominated by linoleic acid (C18:2), which can be associated with the enhancement of tight junction gene expression, considerably increased the expression of CLDN-1, OCLN, and JAM-2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Polyunsaturated fatty acids ( PUFA ), mainly linoleic acid, affect the activity of transcription factors that control the expression of tight junction genes such as CLDN-1 and OCLN, as the result contribute the integrity and permeability of epithelial barrier ( Xu et al, 2021 ). The PUFA content of diet supplemented by BSFLO-SCa was dominated by linoleic acid (C18:2), which can be associated with the enhancement of tight junction gene expression, considerably increased the expression of CLDN-1, OCLN, and JAM-2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…The intestines are the most important organs wherein most nutrients are absorbed ( Feng et al., 2019 ). Desirable dietary interventions targeting parental pigeons are proposed to be a good strategy to facilitate the maintenance of intestinal health status and homeostasis in squabs ( Xu et al., 2020a , b ). It is now generally accepted that intestinal functions are reflected by the intestinal size and structure, especially the villus height and crypt depth.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal functions are usually affected by intestinal morphology such as villus area, villus height, and crypt depth (24). Maternal dietary linoleic acid supplementation has been shown to increase villus area and villus height compared with controls (25). A previous study indicated that linoleic acid deficiency in rats resulted in significantly lower villus height in the ileum compared to controls (26).…”
Section: Discussionmentioning
confidence: 99%